Cold-Sublimating Quasi-Solid Additive Enables High Efficiency and Long Operational Stability Binary Organic Solar Cells - Zhang, Zesheng; Kong, Lingchen; Wang, Xinkang; Wang, Rong; Tang, Hua; Chen, Mingqing; Yang, Yuntong; Zhang, Lianjie; Fu, Yuang; Lu, Xinhui; Ma, Dongge; Lüer, Larry; et al. (Advanced Energy Materials, 2025)
Controlling activelayer morphology during drying is pivotal for the simultaneous realization of high efficiency and durability in Yseries organic solar cells (OSCs). Here, we uncover how the physical state of in situ removable (ISR) isomeric additives, oDF (liquid), mDF (quasisolid), and pDF (solid), governs film formation, molecular ordering, and device stability in binary OSCs. Among them, quasisolid mDF functions as a coldsublimating transient structuring agent: it widens earlystage solvent removal window yet accelerates intermediate crystallization, tightens π–π stacking, enlarges coherence length, and programs a favorable vertical phase separation, as resolved by in situ UV–vis, GIWAXS, and depthprofiled spectroscopy. mDF interacts most strongly with L8-BO while fully evaporating from the film, minimizing nonradiative losses and avoiding the adverse impact of residual additives on device stability. Consequently, PM6:L8BO devices reach 19.28% PCE with improved carrier mobility and suppressed trapassisted recombination; applying mDF to D18:L8BO yields 20.08%. Under 1sun illumination at 70 °C, mDF extends operational stability to T80 = 477 h, outperforming oDF (58 h), pDF (279 h), and additivefree control (103 h). These results establish physicalstateprogrammed ISR additives as a general route to cooptimize efficiency and stability in OSCs and provide mechanistic guidance for scalable, residuefree morphology control.
CRIS-Team Scopus Importer:2025-12-12
Keywords: additive engineering; cold sublimation; in situ removable solid additive; organic solar cell; thermal stability

Highly efficient organic solar cells based on a simple polymer donor derived from a difluorinated benzene-quarterthiophene skeleton - Zhang, Zesheng; Kong, Lingchen; Liu, Chao; Tang, Hua; Wang, Xinkang; Chen, Mingqing; Luo, Mei; Zhang, Lianjie; Liu, Cheng; Liu, Xuncheng; Ma, Dongge; Brabec, Christoph; et al. (Journal of Materials Chemistry C, 2025)
Conjugated polymers with simple chemical structures are essential for the commercialization of organic solar cells (OSCs). However, a simplicity-performance dilemma arises, as current design principles often result in an inverse correlation between these two factors, significantly hindering the commercialization of OSCs. In this study, we investigated the impact of fluorine substitution positions on benzene rings within polythiophenes (PTs), leading to two polymers composed of non-fused rings of o-difluorobenzene-quarterthiophene and p-difluorobenzene-quarterthiophene, namely, Po2F and Pp2F. The Po2F/Y6BO devices achieved a remarkable efficiency of 15.45%, with the active layer fabricated via layer-by-layer (LBL) spin coating, significantly surpassing the Pp2F/Y6BO blend (12.14%) and ranking among the top-performing oligothiophene-based OSCs. The enhancement is mainly attributed to improved phase separation, reduced exciton lifetimes, and suppressed mixing compatibility with Y6BO of Po2F, compared to Pp2F. In addition, the simple polymer Po2F demonstrated a much higher figure of merit (FOM) in chemical accessibility than polymers with fused rings, indicating its great potential for cost reduction. Beyond its role as a donor, Po2F also enhanced the efficiency of PM6:L8BO from 17.74% to 19.05% and extended T80 from 239 to 377 hours when used as an interlayer between the PEDOT:PSS buffer layer and the active layer. This study highlights the significance of a polymer donor-based non-fused ring towards commercially viable OSCs and offers valuable insights for designing high-performance polymers.
CRIS-Team Scopus Importer:2025-04-01